Pengaruh Foreign Direct Investment, Inflasi, Stabilitas Politik Terhadap Neraca Dagang Di Indonesia Tahun 2019 – 2023 - Salsabillah, Via Amelya; Mardani, Ronny Malavia; Bastomi, Mohamad (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to examine the effect of foreign direct investment, inflation rate, political stability on the trade balance in Indonesia. The population in this study is the trade balance ratio registered with the Central Statistics Agency (BPS) in the monthly period from January 2019 to December 2023. By using the saturated sample method, a sample size of 60 was obtained. The type of data used in this study is secondary data. The Ordinary Least Squares (OLS) analysis technique is used to test the interaction of independent variables whether they affect the dependent variable. The results of this study indicate that foreign direct investment and political stability have a significant effect on the trade balance, the inflation rate does not affect the trade balance. Keywords: Foreign Direct Investment, Inflation, Political Stability, Trade Balance